Dicamba use and cancer incidence in the agricultural health study: an updated analysis. (1st May 2020) - Lerro, Catherine C; Hofmann, Jonathan N; Andreotti, Gabriella; Koutros, Stella; Parks, Christine G; Blair, Aaron; Albert, Paul S; Lubin, Jay H; Sandler, Dale P; Beane Freeman, Laura E
Abstract: Background: The herbicide dicamba has been commonly used agriculturally and residentially. Recent approval of genetically engineered dicamba-resistant crops is expected to lead to increased dicamba use, and there has been growing interest in potential human health effects. A prior analysis in the Agricultural Health Study (AHS) suggested associations between dicamba and colon and lung cancer. We re-evaluated dicamba use in the AHS, including an additional 12 years and 2702 exposed cancers. Methods: The AHS is a prospective cohort of pesticide applicators in Iowa and North Carolina. At enrollment (1993–1997) and follow-up (1999–2005), participants reported dicamba use. Exposure was characterized by cumulative intensity-weighted lifetime days, including exposure lags of up to 20 years. We estimated relative risks (RR) and 95% confidence intervals (CI) using multivariable Poisson regression for incident cancers diagnosed from enrollment through 2014/2015. Results: Among 49 922 applicators, 26 412 (52.9%) used dicamba. Compared with applicators reporting no dicamba use, those in the highest quartile of exposure had elevated risk of liver and intrahepatic bile duct cancer ( n exposed = 28, RRQ4 = 1.80, CI: 1.26–2.56, P trend < 0.001) and chronic lymphocytic leukaemia (CLL, n exposed = 93, RRQ4 = 1.20, CI: 0.96–1.50, P trend = 0.01) and decreased risk of myeloid leukaemia ( n exposed = 55, RRQ4 = 0.73, CI: 0.51–1.03, P trend = 0.01). The associations for liver cancer and myeloid leukaemia remained after lagging exposure of up to 20 years. Conclusions: With additional follow-up and exposure information, associations with lung and colon cancer were no longer apparent. In this first evaluation of liver and intrahepatic bile duct cancer, there was an association with increasing use of dicamba that persisted across lags of up to 20 years.